Opposition to Women in Congregational Leadership: A Sociocultural Perspective - Solomon Kofi Amoah; Josephine Semanu Safo; Linda Ama Owusuaa Amoah (Centre for Behaviour and Wellness Advocacy, 2015)
Although many efforts have been made in time past in demonstrating that women are similar to men, there still appear to be a widespread persistent belief that women are indeed inferior to men even until today. What is even worrying is the theological backing that this sociocultural belief of society enjoys. One notices in the literature that God ordains, sanctions, and upholds the spiritual authority of women today as he did in time past as his official spokespersons and leaders of his people. However, the evidence and discussion presented in this paper demonstrate that problems with women being accepted as leaders by congregations, gender differences in pay and promotions, and the experiences and dissatisfaction of women clergy who feel constrained by these gender discrimination is widespread. The paper discusses this phenomenon and presents an often neglected perspective in the discourse - the sociocultural perspective. It interrogates the various stands on women and leadership in congregations. In doing this, the paper explores the position of women in the Old Testament through to the New Testament and the centuries following.